Desain Antena Mikrostrip UWB dengan Peningkatan Lebar pita dan Karakteristik Triple Notch Band - Harfan Hian Ryanu; Dhoni Putra Setiawan; Edwar (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
This paper discusses the design of Ultra-Wideband (UWB) hexagonal monopole planar microstrip antenna with bandwidth enhancement characteristic using hexagonal shaped slot ring EBG and triple notch-band characteristic using three different slots. A hexagonal shaped monopole planar antenna is integrated with an EBG structure in order for the antenna to work at 2,8 -16 GHz bandwidth. A combination of L shaped, horizontal, and round shaped slots with different length are also integrated in the patch to remove three frequency band at WLAN (4,9-6,2 GHz), satellite downlink communication (7,1-7,6 GHz), and Direct Broadcasting Satellite (DBS) (12,2-12,7 GHz). The overall dimension of the antenna is 35,6 mm x 27,3 mm, with a thickness of 1,6 mm. The final design of the antenna shows a good result at frequency band 2,86-16,08 GHz under the reflection coefficient < -10 dB, except at frequency WLAN (5,5 GHz), X-Band satellite (7,45 GHz), and DBS service (12,45 GHz), with maximum gain of 4,8 dBi at 14 GHz, and good antenna efficiency ranged from 45% to 85%.